ESTABLISHING RELIGIOUS FREEDOM: An Overview of the Quran and Hadith in the Indonesian Context (Study of Tafsir Qurais Shihab Qs. Al-Baqarah verse 256) - Nurkamiden, Sukrin; Hanifah, Ida; Waliko, Waliko (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The purpose of this writing is to find out the principle of freedom of religion in order to be able to realize a form of Islamic respect for other religions. The theory used in this research is a theory that views the implementation of religious freedom from the perspective of the Al-Qur'an in the interpretation of Al-Misbah Qs. Al-Baqarah Verse 256 and Hadith. This research is qualitative research with several interpretation methods, one of which is the Quraish Shihab interpretation method. The data in this research is through tolerance verses in the tafsir al-Misbah and hadith which explain tolerance starting from various explanations about the principles, attitudes or ethics of the Koran towards non-Muslims in terms of tolerance towards religious freedom. The results of this research show an understanding of the principle of freedom of religion. This is an illustration of religious communities implementing the principles of religious freedom, especially in Indonesia. Because basically freedom of religion is sunatullah, but when we have chosen a religion, then religious freedom is bound by the rules of that religion, and has been regulated by the state in the constitution. Meanwhile, respecting other religions, especially Islam towards other religions, is a must, even obligatory, because Islamic teachings allow its followers to collaborate with non-Muslims, as long as it does not involve matters of faith or at a theological level.